PENGEMBANGAN PEMASARAN DIGITAL MELALUI SISTEM INFORMASI BERBASIS WEBSITE SERTA MEDIA SOSIAL PADA UMKM SOSOXEWA BIBIT BUAH MAKASSAR - Rizky Inayah Muflih Ramadani; Muhammad Ashdaq; Valentino Aris (JURNAL KINDAI, 2026)
Abstract: This study aims to develop a website-based information system integrated with social media to increase the promotional effectiveness of the Sosoxewa Bibit Buah Makassar MSME. Observations show that most MSMEs only utilize social media separately without the support of a website-based information system, which results in suboptimal access to product information and business credibility in Makassar City. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The website was developed as a product catalog and business information center integrated with a Facebook business page. Evaluation was carried out using the System Usability Scale (SUS) and digital marketing metric analysis. The results showed a SUS score of 81.43, which is in the good category, where the SUS score range is 0-100. Digital performance data also showed an increase in visibility, with 12,693 organic content impressions, 1,664 clicks to the website, and an engagement rate of 5.3%. These findings indicate that integrating a website-based information system with a social media strategy is effective in increasing promotional reach and ease of access to MSME product information. Keywords: ADDIE; digital marketing; MSME; social media; website-based information system